A highly-integrated fractional-N synthesizer for FMCW radar - Eickhoff, Ralf; Ellinger, Frank; Ußmüller, Thomas; Spiegel, Solon (IEEE International Conference on Microwaves, Communications, Antennas and Electronic Systems, 2008, 2008)
This paper presents an integrated synthesizer for frequency ramp generation in local positioning systems using frequency modulated continuous wave (FMCW) radar in the ISM band at 5.8 GHz. The synthesizer is designed and implemented as a fractional-N phase locked loop (PLL) in a 0.18 mum SiGe-BiCMOS technology controlled by a MASH 1-1-1 SigmaDelta-modulator, which is integrated on an FPGA. Besides preventing spurs in the output spectrum, this digital control allows a flexible programming of the synthesizer with respect to its frequency ramp generation and output spectrum respectively. The complete fractional-N synthesizer was integrated into a single system PCB and measurements regarding phase noise and tuning range were performed. Moreover, an FMCW radar system using this synthesizer achieved an accuracies of 13 cm in indoor environments.
elib2cris::1512001600,eickhoff2008b